Early-life maturation of the somatosensory cortex: sensory experience and beyond - Nwabudike, Ijeoma; Che, Alicia (Frontiers in Neural Circuits, 2024)
Early life experiences shape physical and behavioral outcomes throughout lifetime. Sensory circuits are especially susceptible to environmental and physiological changes during development. However, the impact of different types of early life experience are often evaluated in isolation. In this mini review, we discuss the specific effects of postnatal sensory experience, sleep, social isolation, and substance exposure on barrel cortex development. Considering these concurrent factors will improve understanding of the etiology of atypical sensory perception in many neuropsychiatric and neurodevelopmental disorders.